Nitrate Legacy in a Tropical and Complex Fractured Volcanic Aquifer System - Sánchez-Gutiérrez, Rolando (2023)
Nitrate legacy is affecting groundwater sources across the tropics. This study describes isotopic and ionic spatial trends across a tropical, fractured, volcanic multi-aquifer system in central Costa Rica in relation to land use change over four decades. Springs and wells (from 800 to 2,400 m asl) were sampled for NO3 − and Cl − concentrations, δ 18Owater, δ 15NNO3, and δ 18ONO3. A Bayesian isotope mixing model was used to estimate potential source contributions to the nitrate legacy in groundwater. Land use change was evaluated using satellite imagery from 1979 to 2019. The lower nitrate concentrations (<1 mg/L NO3 −N) were reported in headwater springs near protected forested areas, while greater concentrations (up to ∼63 mg/L) were reported in wells (mid- and low-elevation sites in the unconfined unit) and low-elevation springs. High-elevation springs were characterized by low Cl − and moderate NO3 −/Cl − ratios, indicating the potential influence of soil nitrogen (SN) inputs. Wells and low-elevation springs exhibited greater NO3 −/Cl − ratios and Cl − concentrations above 100 μmol/L. Bayesian calculations suggest a mixture of sewage (domestic septic tanks), SN (forested recharge areas), and chemical fertilizers (coffee plantations), as a direct result of abrupt land use change in the last 40 years. Our results confirm the incipient trend in increasing groundwater nitrogen and highlight the urgent need for a multi-municipal plan to transition from domestic septic tanks to regional sewage treatment and sustainable agricultural practices to prevent future groundwater quality degradation effectively.